Chronic Morbidity Among Older Children and Adolescents at Diagnosis of HIV Infection. (1st November 2016) - McHugh, Grace; Rylance, Jamie; Mujuru, Hilda; Nathoo, Kusum; Chonzi, Prosper; Dauya, Ethel; Bandason, Tsitsi; Simms, Victoria; Kranzer, Katharina; Ferrand, Rashida A.
Abstract : Background: Substantial numbers of children with HIV present to health care services in older childhood and adolescence, previously undiagnosed. These "slow-progressors" may experience considerable chronic ill health, which is not well characterized. We investigated the prevalence of chronic morbidity among children aged 6–15 years at diagnosis of HIV infection. Methods: A cross-sectional study was performed at 7 primary care clinics in Harare, Zimbabwe. Children aged 6–15 years who tested HIV positive following provider-initiated HIV testing and counseling were recruited. A detailed clinical history and standardized clinical examination was undertaken. The association between chronic disease and CD4 count was investigated using multivariate logistic regression. Results: Of the 385 participants recruited [52% female, median age 11 years (interquartile range 8–13)], 95% were perinatally HIV infected. The median CD4 count was 375 (interquartile range 215–599) cells per cubic millimeter. Although 78% had previous contact with health care services, HIV testing had not been performed. There was a high burden of chronic morbidity: 23% were stunted, 21% had pubertal delay, 25% had chronic skin disease, 54% had a chronic cough of more than 1 month-duration, 28% had abnormal lung function, and 12% reported hearing impairment. There was no association between CD4 count of <500 cells per cubic millimeter or <350 cells per cubic millimeter with WHO stage or these chronic conditions. Conclusions: In children with slow-progressing HIV, there is a substantial burden of chronic morbidity even when CD4 count is relatively preserved. Timely HIV testing and prompt antiretroviral therapy initiation are urgently needed to prevent development of chronic complications.